Determinants of health-related quality of life in young adults living with perinatally acquired HIV infection in Botswana - Grace Karugaba; Gloria Thupayagale-Tshweneagae; Mary M. Moleki; Onkabetse V. Mabikwa; Mogomotsi Matshaba (AOSIS, 2022)
Background: Due to the successful antiretroviral therapy (ART) programme in Botswana, large numbers of perinatally HIV-infected adolescents are emerging into young adulthood. Young adulthood is a critical period of human development. However, there is lack of information on the factors affecting the health-related quality of life (HRQOL) of young adults living with perinatally acquired HIV (YALPH) in Botswana. Objectives: The objective of this study was to assess the HRQOL and its determinants among YALPH who were enrolled on ART at Botswana-Baylor Children's Clinical Centre of Excellence in Gaborone, Botswana. Method: A cross-sectional study assessed the HRQOL of 509 YALPH aged 18-30 years using the WHOQOL-HIV BREF. Data about other variables of interest were abstracted from medical records. Bivariate analyses were performed using t and Chi-square tests to determine the associations between demographic and clinical variables and general HRQOL. The variables that were associated with the general HRQOL at P-value 0.1 were included in the multivariable analysis using the logistic regression approach. Results: The majority of participants had good general HRQOL (78.4%). The highest mean HRQOL score was in the Physical domain (5.4 [± 2.9]) and the lowest in the Environment domain (13.8 [± 2.7]). The factors that were significantly associated with the general HRQOL included: level of education attained (P = 0.012), employment status (P = 0.069), viral load suppression (P = 0.073) and self-reported illness (P = 0.001). Conclusion: Interventions that effectively increase educational attainment, employment opportunities, ART adherence, and prevention or management of illness are needed to promote good HRQOL among YALPH in Botswana.